Spectrum of invasive critical procedures performed by clinical fellows in the pediatric intensive care unit of a developing country - Bibi Qurat-; Sadiq Mirza; Anwarul Haque; Murtaza Gova; Majid Shahani; Shahzad Munir; Faiza Rehman; Abdul Rahim Ahmad (Wolters Kluwer Medknow Publications, 2020)
Objective: The objective of this study is to describe the frequency of invasive critical procedures (ICPs) performed by pediatric critical care medicine (PCCM) fellows during their training period. Design: This was a retrospective study. Setting: This was a multidisciplinary, closed 6-bed pediatric intensive care unit (PICU) staffed by four pediatric critical care physicians. Methods: We reviewed the electronic medical record and logbook of each fellow from January 2018 to December 2019. Two most commonly performed ICPs included in this study were endotracheal intubation and ultrasound-guided central venous catheter (USG-CVC) insertion. Demographic data and details of ICPs performed were collected on a structured data collection sheet. The primary outcome was the frequency of ICPs performed by clinical fellows during the training period and their success rate. Results: Of the total 1080, 352 ICPs were performed on 560 (51.8%) patients by four PCCM fellows during the 2-year period. Only two most commonly performed procedures, i.e., ET-intubation and UG-CVC insertion were included in this study. These ICPs comprised of endotracheal tube placement (52.85%, n = 186) and USG central venous line insertion (47.15%, n = 166). About 64.4% of patients were under 5 years, 56% were male, and 72% were admitted with cardiorespiratory failure. The frequency of endotracheal intubation was 23/fellow/year and USG-CVC insertion was 21/fellow/year and the success rate was >90%. Conclusion: Our clinical fellows performed adequate numbers of endotracheal intubation and USG-CVC insertion to achieve competency of procedural skills during their training period.